X linked mental retardation: a clinical guide - Raymond, F L (BMJ Group, 2006)
Mental retardation is more common in males than females in the population, assumed to be due to mutations on the X chromosome. The prevalence of the 24 genes identified to date is low and less common than expansions in FMR1, which cause Fragile X syndrome. Systematic screening of all other X linked genes in X linked families with mental retardation is currently not feasible in a clinical setting. The phenotypes of genes causing syndromic and non‐syndromic mental retardation (NLGN3, NLGN4, RPS6KA3(RSK2), OPHN1, ATRX, SLC6A8, ARX, SYN1, AGTR2, MECP2, PQBP1, SMCX, and SLC16A2) are first discussed, as these may be the focus of more targeted mutation analysis. Secondly, the relative prevalence of genes causing only non‐syndromic mental retardation (IL1RAPL1, TM4SF2, ZNF41, FTSJ1, DLG3, FACL4, PAK3, ARHGEF6, FMR2, and GDI) is summarised. Thirdly, the problem of recurrence risk where a molecular genetics diagnosis has not been made and what proportion of the male excess of mental retardation is due to monogenic disorders of the X chromosome are discussed.